(untitled) (ANGON: Journal of Animal Science and Technology, 2020)
Backgorund. Strategy to Increase Adoption of Waste Processing Technology in Beef Cattle Farmers in Bawang District, Banjarnegara Regency. Beef cattle population was still quite a large population in the District of Bawang, so there was the potential for livestock manure waste which has great potential to be utilized. Breeders intend to earn income by only selling livestock and have not been able to optimize livestock manure waste. If the use of manure is managed effectively and efficiently, it will produce organic fertilizers with high economic value. This can increase the utilization of livestock manure, increase income and reduce environmental pollution. The study was conducted on March 16-29, 2020 and located in Bawang District, Banjarnegara Regency. The research aims to determine the stage where farmers are in the adoption process, identify strengths, weaknesses, opportunities and threats in the process of waste treatment technology, strategies for improving waste treatment technology. Materials and Methods. The study used a survey method with a sampling method that was conducting interviews using questionnaires. The sampling technique consists of two stages: the first stage of determining the area sample was done by purposive sampling method (intentionally). The second stage was the sampling technique of respondents carried out by the census method of breeders with 40 respondents. Conditions for farmers a minimum of 1 year breeders and have at least one head of cattle found in the villages of Winong, Kutayasa and Majalengka. Research using a questionnaire with a Likert scale. Analysis using SWOT analysis by formulating strategies using SWOT matrix analysis. Results. The results of the stages of adoption of waste treatment technology in Bawang sub-district breeders, the majority of farmers were in the stage of evaluation means that they already have an awareness of interest, evaluation in livestock waste treatment technology, but do not know the impact further. The solution given was that farmers must provide time and energy in waste treatment and the courage to try to make independent organic fertilizer. The chosen strategy was improve breeders’ knowledge and skills so that breeders are more capable and interested in processing livestock manure waste.